Comment on the Stages of HIV Care Continuum: Considering Treatment for Secondary Prevention among Patients ‘Retained in Care’ - Elsa Larson, H.; Candace Frater, S.; A. Lally, Michelle (Journal of Clinical Research In HIV AIDS And Prevention, 2014)
This commentary argues for incorporating secondary prevention into the HIV care continuum for patients retained in care. It outlines opportunities to reduce transmission through viral suppression, risk reduction counseling, and supportive services within routine visits.
Keywords: HIV Care Continuum; Secondary Prevention; Viral Suppression; Risk Reduction Counseling; Transmission